Closure of persistent oro-nasal fistula with removable obturator denture - Đorđević Nadica S.; Ajduković Zorica R.; Milićević Jelena D.; Petrović Milica B.; Pešić Zoran U. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2012)
Introduction. Cleft lip and cleft palate are relatively common congenital deformities. Patients with clefts require multidisciplinary treatment approach and a team which may include a maxillofacial surgeon, orthodontist, speech therapist, pediatrician, prosthetician, psychologist, as well as the relevant experts who may be of help in restoring the function of the orofacial system. Case report. The paper describes a case of prosthetic rehabilitation of an edentulous female patient with oronasal fistula, after multiple surgical interventions performed in various medical institutions in order to treat her cleft primary and secondary palate. Conclusion. Well planned prosthetic treatment of adult patients with cleft palate and total edentulousness can produce satisfactory results in view of both function and esthetics.